Sex Acts in La Celestina: An Ars Combinatoria of Desire - Bidwell-Steiner, Marlen (Renaissance and Reformation / Renaissance et Réforme, 2015)
This article investigates one of the most important and erotically explicit early modern Spanish texts: Fernando de Rojas’s La Celestina (1499/1507). Highlighting the dynamics of the three sex acts depicted in the plot, it argues that intercourse can be read as a negotiation of the text’s main values: (courtly) love, honour, and money. While scholars have elaborated on the metaphor of the wheel of fortune in La Celestina, this article suggests that the wheel was more than a trope for life’s vicissitudes; it operated as a structural tool in the text, a metaphor rendered material via Ramón Llull’s (ca. 1232–1315) ars combinatoria. Applying the Catalan philosopher’s mnemonic device demonstrates how the text’s values are transferred from men to women and thereby shift their semantics. While the resulting inversions must have amused contemporary audiences, they also reveal the tensions of a transforming society.